Prevalence, clinical characteristics and long-term outcomes of classical 11 β-hydroxylase deficiency (11BOHD) in Turkish population and novel mutations in CYP11B1 gene. Issue 181 (July 2018) - Baş, Firdevs; Toksoy, Güven; Ergun-Longmire, Berrin; Uyguner, Zehra Oya; Abalı, Zehra Yavaş; Poyrazoğlu, Şükran; Karaman, Volkan; Avcı, Şahin; Altunoğlu, Umut; Bundak, Ruveyde; Karaman, Birsen; Başaran, Seher; et al.
Graphical abstract: A 3D structure of Cytochrome P450 11B1. Positions of all the coding region mutations in our cases are pointed by arrow, and marked by purple color for easy identification. Highlights: In CYP11B1 gene 13 different mutations were identified in 25 Turkish families (4 novel). p.Leu299Pro was the most common mutation in our 11BOHD cohort. There was phenotypic variability among the patients with the same mutations. Three dimensional protein simulations may provide additional support for pathogenicity of genetic alterations. Abstract: Congenital adrenal hyperplasia (CAH) due to 11β-hydroxylase deficiency (11BOHD) is a rare autosomal recessive disorder and the second most common form of CAH. Aim: To investigate genotype-phenotype correlation and to evaluate clinical characteristics and long-term outcomes of patients with 11BOHD. Methods: A total of 28 patients (n = 14, 46, XX; n = 14, 46, XY) with classical 11BOHD from 25 unrelated families were included in this study. Screening of CYP11B1 is performed by Sanger sequencing. Pathogenic features of novel variants are investigated by the use of multiple in silico prediction tools and with family based co-segregation studies. Protein simulations were investigated for two novel coding region alterations. Results: The age at diagnosis ranged from 6 days to 12.5 years. Male patients received diagnose at older ages than female patients. The rate of consanguinity was high (71.4%). Five out of nine 46, XX patients were diagnosed late (age 2–8.7 years) and were assigned as male due to severe masculinization. Twenty one patients have reached adult height and sixteen were ultimately short due to delayed diagnosis. Two male patients had testicular microlithiasis and 5 (35.7%) patients had testicular adrenal rest tumor during follow up. Four patients (28.6%) had gynecomastia. Mutation analyses in 25 index patients revealed thirteen different mutations in CYP11B1 gene, 4 of which were novel (c.393 + 3A > G, c.428G > C, c.1398 + 2T > A, c.1449_1451delGGT). The most frequent mutations were c.896T > C with 32%, c.954G > A with 16% and c.1179_1180dupGA with 12% in frequency. There was not a good correlation between genotype and phenotype; phenotypic variability was observed among the patients with same mutation. Conclusion: This study presents the high allelic heterogeneity of CYP11B1 mutations in CAH patients from Turkey. Three dimensional protein simulations may provide additional support for the pathogenicity of the genetic alterations. Our results provide reliable information for genetic counseling, preventive and therapeutic strategies for the families.